Effect of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Ney, Shannon P.; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
Newborn piglets are born with inadequate iron stores and are not able to receive the proper amount of iron in their mother’s milk thus resulting in iron deficiency. Iron deficiency in newborn piglets results in anemia and eventually death if not given a proper injection of iron dextran. Gleptoferron, also known as GleptoForte is another form of iron and is considered to be at least equivalent to iron dextran. The purpose of this experiment was to evaluate the effects of increasing the dosage of GleptoForte in newborn pigs on sow and litter performance. To complete this experiment, a 21-d farrowing study was conducted using 336 newborn pigs (DNA making a total of 28 litters being utilized. On the day of processing (d 3 after birth) piglets were weighed and six barrows and six gilts per litter were then allotted to a treatment in a completely randomized design totaling 56 piglets per treatment. The treatment process consisted of a negative control which regarded to receiving no iron injection and increasing levels of GleptoForte at 50, 100, 150, 200, or 200 mg plus a 100 mg booster at d 11 of farrowing. On d 3 (processing day), d 11, and d 21 (weaning), piglets were weighed to calculate the average daily gain (ADG) during farrowing as well as one barrow per litter per treatment was used for blood collection via jugular venipuncture to attain proper blood criteria which consisted of: Hemoglobin (Hgb), Hematocrit (Hct), Serum Fe, and Total Iron Binding Capacity (TIBC). In the long-run, ADG increased in piglets (quadratic; P = 0.002) with an increasing dosage of GleptoForte as well as an increase in BW on d 11 (quadratic; P = 0.018). In the end, the ending ADG and BW improved on d 21 (quadratic; P = 0.001). When 100 mg of GleptoForte was administered resulted in the greatest performance while the injection of 200 mg + 100 mg of GleptoForte improved the hematological criteria however did not improve suckling piglet growth performance as compared to 200 mg alone.
Keywords: Fall 2017